EFFECT OF RED ONION (ALLIUM CEPA VAR. AGGREGATUM G. DON) ON SERUM URIC ACID LEVEL AND TOTAL ANTIOXIDANT STATUS IN NORMAL AND INDUCED HYPERURICEMIC RATS - Rahmat, Asmah; Yen Leng, Choo; Abu Bakar, Fazleen Izzany; Abu Bakar, Mohd Fadzelly (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: This study aimed to investigate the effect of onion (Allium cepa var. aggregatum G. Don) on serum uric acid level and total antioxidant status of normal and induced hyperuricemic rats. Methods: A total of 36 male Sprague-Dawley rats were divided equally into six groups, and 250 mg/kg of potassium oxonate was injected intraperitoneally on day 1, 3, and 7 to induce hyperuricemia in rats. 7 d consecutively of treatment were given to the rats by oral gavage. Serum uric acid level was measured 2 h after the induction on day 1, 3, 7, and 14. Blood plasma was obtained at day 14 to measure its total antioxidant status. The rats were sacrificed by taking out their liver and kidney for histopathological evaluation. Results: The results showed that onion juice lowered the serum uric acid level in dose-dependent manner. The highest dose (10.5 g/kg/day) appeared to possess the inhibitory effect almost similar to allopurinol. There was an increase in total antioxidant status in a hyperuricemic group treated with onion juice compared to control groups but insignificant. By viewing the histological profile, onion showed to have a protective effect toward the liver damage by hyperuricemia. However, this was not happened in kidney. Conclusion: Onion lowered the serum uric acid level, but its protective effect toward liver and kidney remained ambiguous. Further investigation with the increase of parameters and inclusion of analytical test of bioactive compound in red onion is recommended for the future studies.